NEGATIVE TRANSFER OF IDIOMATIC EXPRESSIONS FROM ARABIC TO ENGLISH: A PSYCHOLINGUISTIC STUDY - Hlail, Mohammed Hussein (International Journal of Psychosocial Rehabilitation, 2020)
This paper sheds the light on the analysis of idiomatic expressions used in essays or written tests submitted by Iraqi-speaking second-year, college of education , Maysan University. Those students are learning English language as a foreign language. The present study aims at showing the negative transfer of idiomatic expressions used by those Arabic students into English. Also it aims to identify and classify the idiomatic expressions. The present study comes with some results concerning the idiomatic expressions whether from lexical, grammatical or syntactic point of view, some of them are: Formally and semantically similar. Similar in structure and the content. Formally similar, semantically different. Differ in meaning rather than the form.